Pemantauan Ruangan Melalui Infrastruktur Internet Messaging Dengan Menggunakan Aplikasi IOT - U Darmanto Soer; Dadang Heri Kusuma (The Faculty of Science and Technology, 2019)
Room security is vital for many people. It has become everyone's need if a room needs to beequipped with security equipment or has a tool to monitor the room or residence. Therefore weneed a tool to monitor the room. Surveillance camera is one solution to be able to record eventsthat occur in the monitored room.This system combines the use of the Raspberry Pi cameramodule, infrared sensor, and Rasspberry Pi in order to find out the condition of the room in theform of images if a motion is detected and also the use of the Bot feature on the internet messagingapplication, Telegram. This system is more efficient because it uses Telegram's storage.And alsomore effective because the system will send notifications via Telegram Bots. So that the user cantake action as soon as possible if an unwanted condition occurs